Engaging at the science-policy interface as an early-career researcher: experiences and perceptions in biodiversity and ecosystem services research. Issue 1 (31st December 2022) - Filyushkina, Anna; Ryu, Hyeonju; Kadykalo, Andrew N.; Murali, Ranjini; Campagne, C. Sylvie; Washbourne, Carla-Leanne; Peter, Sophie; Saidi, Nada; Sarzynski, Thuan; Fontanella Pisa, Paola; Ávila-Flores, Giovanni; Amiar, Taha
ABSTRACT: Effective knowledge exchange at science-policy interfaces (SPIs) can foster evidence-informed policy-making through the integration of a wide range of knowledge inputs. This is especially crucial for conservation and sustainable use of biodiversity and ecosystem services (ES), human well-being and sustainable development. Early-career researchers (ECRs) can contribute significantly to knowledge exchange at SPIs. Recognizing that, several capacity building programs focused on sustainability have been introduced recently. However, little is known about the experiences and perceptions of ECRs in relation to SPIs. Our study focused on SPI engagement of ECRs who conduct research on biodiversity and ES, as perceived and experienced. Specifically, we addressed 'motivations', 'barriers' and 'opportunities and 'benefits'. A total of 145 ECRs have completed the survey. Our results showed that ECRs were generally interested to engage in SPIs and believed it to be beneficial in terms of contributing to societal change, understanding policy processes and career development. Respondents perceived lack of understanding about involvement channels, engagement opportunities, funding, training, perceived credibility of ECRs by other actors and encouragement of senior colleagues as barriers to engaging in SPIs. Those who have already participated in SPIs generally saw fewer barriers and more opportunities. A key reason for dissatisfaction with experience in SPIs was a lack of impact and uptake of science-policy outputs by policymakers – an issue that likely extends beyond ECRs and implies the need for transformations in knowledge exchange within SPIs. In conclusion, based on insights from our survey, we outline several opportunities for increased and better facilitation of ECR engagement in SPIs.